STRATEGIC PATHWAYS TO MINIMAL DETERRENCE AND COUNTER-TERRORISM: ENHANCING BRUNEI’S DEFENSE CAPABILITIES - Lee, Brice Tseen Fu; Komšić, Filip; Sims, Juan Pablo (Journal of Terrorism Studies, 2024)
This paper explores the strategic enhancement of Brunei’s military capabilities under the guidelines of the Brunei Defense White Paper 2021, focusing on establishing a robust minimal level deterrence. It emphasizes transitioning from conventional defense paradigms to an integrated, technologically advanced military structure tailored to contemporary and future security challenges. The significance of minimal level deterrence is analyzed, illustrating how a proportionate and efficient military force not only deters potential aggressors but also supports counter-terrorism efforts. This approach underscores the dual benefits of ensuring national security while facilitating economic stability and growth, allowing Brunei to allocate resources more effectively between defense and development sectors. The discussion extends to how Brunei can optimize its defense expenditure by investing in high-impact technologies that enhance capability across air, land, and naval forces without necessitating a large military footprint. The paper argues that such strategic investments not only bolster national and regional security but also enhance Brunei's international standing by contributing to a stable Southeast Asian region. The integration of advanced technologies and a focus on multi-domain operations are proposed as key strategies for maintaining security and supporting economic objectives.